Effect of dwell condition on fatigue behavior of a high-Nb TiAl alloy at 750 °C. (December 2017) - Dong, Chengli; Jiao, Zehui; Yu, Huichen; Zhou, Haitao; Kong, Fantao; Chen, Yuyong
Abstract: The strain-controlled low cycle fatigue (LCF) and creep-fatigue interaction (CFI) tests of a newly developed Ti-45Al-8Nb-0.2W-0.2B-0.02Y (at.%) alloy were carried out at 750 °C in air. The hysteresis loop, cyclic stress response and life modeling as well as failure mechanism of the alloy were investigated in detail. It was revealed that the tensile and compressive mean stresses would generate when the dwell condition was introduced at minimum and maximum strain, respectively. In addition, the dwell condition, especially for the compressive dwell condition, would significantly decrease the fatigue life. The typical continuum damage accumulation(CDA) and modified CDA life models proposed in the present study were employed to predict both LCF and CFI life of the alloy, which showed that the modified CDA life model had a higher accuracy than the typical CDA life one. Moreover, only single crack initiation source was observed at 92% ( i.e. 11/12) of LCF fracture while multiple crack initiation sources at 84% ( i.e. 31/37) of CFI fracture. Apparently different from LCF specimen showing more transgranular appearance, CFI specimen shows more intergranular appearance. Highlights: Different dwell times and forms were considered at CFI tests at the same time. Tensile and compressive dwell produced compressive and tensile mean stress. The dwell condition would decrease the fatigue life at 750 °C. The modified CDA life model had a higher accuracy than the typical CDA life one.